Pengaruh Etos Kerja Terhadap Kualitas Pelayanan Terpadu Satu Pintu (PTSP) Pada Kementerian Agama Kota Surabaya - Alisiya, Elinda Millenia; Fikriyah, Khusnul (Universitas Negeri Surabaya, 2022)
This study aims to determine and analyze the implementation of the work ethic of the One Stop Integrated Service (PTSP) and the influence of the work ethic on the service quality of the One Stop Integrated Service (PTSP) at the Ministry of Religion of the City of Surabaya. This type of research uses a quantitative approach with primary data sources in the form of short interviews and questionnaires. The population of this study are service recipients at the Ministry of Religion of the City of Surabaya who are domiciled and have an ID card in the City of Surabaya, while the number of samples required is 45 respondents using a non-probability sampling technique in the form of purposive sampling. This study was tested using data testing on SPSS version 24. The results of this study using a simple linear regression test showed that there was an effect of work ethic on service quality, while the T test hypothesis test showed that partially work ethic had no effect on service quality.